2002
DOI: 10.1242/dev.129.12.2957
|View full text |Cite
|
Sign up to set email alerts
|

abdominal Aspecifies one cell type inDrosophilaby regulating one principal target gene

Abstract: The Hox/homeotic genes encode transcription factors that generate segmental diversity during Drosophila development. At the level of the whole animal, they are believed to carry out this role by regulating a large number of downstream genes. Here we address the unresolved issue of how many Hox target genes are sufficient to define the identity of a single cell. We focus on the larval oenocyte, which is restricted to the abdomen and induced in response to a non-cell autonomous, transient and highly selective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The Drosophila larval oenocytes are specialised cells that form in clusters beneath the developing epidermis, and play roles in the synthesis and metabolism of lipids and hydrocarbons (reviewed in [ 58 ]). It had previously been shown that binding of Abd-A to a rhomboid (rho) cis-regulatory module is required for the formation of larval oenocytes [ 59 , 60 ], this process was further investigated by Li-Kroeger and colleagues (2012) who discovered that complex interplay between Abd-A and its co-factors is required for the formation of these specialised cells [ 61 ]. In this context, it appears that Abd-A forms an activating complex composed of Hth, Exd and Pax2.…”
Section: Hox Gene Regulation Of Fine-scale Phenotypes In Dr...mentioning
confidence: 99%
“…The Drosophila larval oenocytes are specialised cells that form in clusters beneath the developing epidermis, and play roles in the synthesis and metabolism of lipids and hydrocarbons (reviewed in [ 58 ]). It had previously been shown that binding of Abd-A to a rhomboid (rho) cis-regulatory module is required for the formation of larval oenocytes [ 59 , 60 ], this process was further investigated by Li-Kroeger and colleagues (2012) who discovered that complex interplay between Abd-A and its co-factors is required for the formation of these specialised cells [ 61 ]. In this context, it appears that Abd-A forms an activating complex composed of Hth, Exd and Pax2.…”
Section: Hox Gene Regulation Of Fine-scale Phenotypes In Dr...mentioning
confidence: 99%
“…Intriguingly, Abd-A regulates these two CRMs in different cell types and in opposing ways. In the developing peripheral nervous system, Abd-A triggers the secretion of epidermal growth factor ligands from a specific subset of abdominal sensory organ precursor cells by activating the expression of the rhomboid ( rho ) serine protease gene via a highly conserved CRM called RhoA ( Brodu et al, 2002 ; Li-Kroeger et al, 2008 ). In contrast, Abd-A, as well as Ubx, suppresses leg development in abdominal segments by repressing the expression of the Distal-less ( Dll ) homeodomain protein in ectodermal cells via the Dll conserved regulatory element ( DCRE ) ( Vachon et al, 1992 ; Gebelein et al, 2002 , Gebelein et al, 2004 ).…”
Section: Case Studies On the Cis -Regulatory Logic Of Hox Transcription Factorsmentioning
confidence: 99%
“…First, the same Hox, Exd, and Hth binding sites are capable of mediating either activation or repression. The RhoA CRM contains a single set of adjacent Exd/Hth/Hox binding sites ( Figure 3B ; Brodu et al, 2002 ; Li-Kroeger et al, 2008 ), whereas the DCRE CRM contains three Hox sites, each of which is directly adjacent to a Exd or Hth site ( Figures 3C,E ; Gebelein et al, 2002 , Gebelein et al, 2004 ; Uhl et al, 2016 ). Each configuration of binding sites is capable of cooperatively binding Abd-A/Hth/Exd complexes.…”
Section: Case Studies On the Cis -Regulatory Logic Of Hox Transcription Factorsmentioning
confidence: 99%
“…Hox genes also play more subtle but important post-embryonic roles in regulating cell identify to sculpt the fine-scale morphology of structures and organs, and consequently have been likened to “micromanagers” ( Akam, 1998a ; Akam, 1998b ; Hombría and Lovegrove, 2003 ; Buffry and McGregor, 2022 ). Several such post-embryonic roles of Hox genes have been identified in Drosophila ; for example, the specification of certain subtypes of cells in the central nervous system ( Kannan et al, 2010 ; Estacio-Gómez et al, 2013 ), the regulation of the development of larval oenocytes by abdominal-A ( abd-A ) ( Brodu et al, 2002 ), and the integration of regulatory information to specify differences in prothoracic (T1) leg bristle patterning among leg segments and between sexes by Sex-combs reduced ( Scr ) ( Eksi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%